Dynamics of the Digital Workforce: Assessing the Interplay and Impact of AI, Automation, and Employment Policies - Oluwaseun Oladeji Olaniyi; Favour Amarachi Ezeugwa; Chinenye Gbemisola Okatta; Abayomi Shamsudeen Arigbabu; Princess Chimmy Joeaneke (Archives of Current Research International, 2024)
The rapid integration of artificial intelligence (AI) and automation within various sectors poses challenges and opportunities for the global workforce. This study investigates the implications of AI and automation on employment patterns, skills requirements, and remote work infrastructures. Employing a quantitative research design, data was collected through a structured questionnaire administered to 482 professionals across the information technology, healthcare, and finance sectors. The analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) to test hypotheses related to the impact of technological advancements on employment. Major findings indicate a significant, albeit complex, impact of AI and automation on employment. Most respondents recognized AI and automation as catalysts for creating new job opportunities and enhancing productivity, particularly in sectors with high integration of digital technologies. However, the study also highlighted substantial concerns regarding the widening skills gap and the adequacy of current employment policies in managing the transition. Specifically, sixty-nine percent of respondents identified a significant skills gap necessitating urgent educational and training interventions. About half of the respondents viewed existing employment policies as inadequate in addressing the challenges of rapid technological changes. The study concludes that while AI and automation are reshaping the employment landscape, creating new types of jobs, and altering skill requirements, there is a critical need for proactive adaptation strategies. Recommendations include developing targeted reskilling programs, adaptive employment policies, and robust remote work infrastructures to support an increasingly digital workforce. These strategies are essential to harness the benefits of digital transformations while mitigating potential adverse effects on employment.